2017
DOI: 10.2174/1874149501711010270
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength Study on the Freeze-thaw Resistance of Recycled Aggregate Concrete Members

Abstract: Introduction:Freeze-thaw resistance of recycled aggregate concrete with partial or total replacement of recycled aggregate compared with that of natural aggregate concrete was investigated in this paper. Method:Ninety specimens were fabricated to study the influence of different recycled aggregate replacement ratios on the surface scaling, mass loss, and residual compressive strength after 100 freeze-thaw cycles. Results:The experiment results indicate that the type of recycled aggregate and its replacement ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, most scholars believe that, due to the unique properties of recycled coarse aggregate, if the substitution rate continues to increase, the degree of deterioration of frost resistance of recycled concrete will continue to decline. Niu Haicheng et al [24] found that the frost resistance of recycled concrete decreases with the increase of the substitution rate of recycled coarse aggregate, and the relative dynamic elastic modulus of fully recycled concrete has been more than 10% lower than that of ordinary concrete after 100 freeze-thaw cycles. Wei Chengjuan et al [25] prepared high-strength recycled concrete mixed with 0%, 40%, 60%, 80% and 100% recycled coarse aggregate, and the replacement rate of recycled coarse aggregate did not show a significant effect when the freeze-thaw cycle was lower than 200 times, but the relative dynamic elastic modulus decreased more and more significantly with the increase of the replacement rate when it was higher than 200 times.…”
Section: Coarse Aggregate Admixturementioning
confidence: 99%
“…However, most scholars believe that, due to the unique properties of recycled coarse aggregate, if the substitution rate continues to increase, the degree of deterioration of frost resistance of recycled concrete will continue to decline. Niu Haicheng et al [24] found that the frost resistance of recycled concrete decreases with the increase of the substitution rate of recycled coarse aggregate, and the relative dynamic elastic modulus of fully recycled concrete has been more than 10% lower than that of ordinary concrete after 100 freeze-thaw cycles. Wei Chengjuan et al [25] prepared high-strength recycled concrete mixed with 0%, 40%, 60%, 80% and 100% recycled coarse aggregate, and the replacement rate of recycled coarse aggregate did not show a significant effect when the freeze-thaw cycle was lower than 200 times, but the relative dynamic elastic modulus decreased more and more significantly with the increase of the replacement rate when it was higher than 200 times.…”
Section: Coarse Aggregate Admixturementioning
confidence: 99%
“…However, research results show that there are still difficulties and drawbacks of using recycled aggregates in concrete. Studies have found that the performance of recycled aggregate concrete is lower than that of natural aggregate concrete, and there are also durability problems [7][8][9]. Moreover, compared with natural aggregate, recycled aggregate has higher water absorption and lower density, which reduces the mechanical properties of concrete to a certain extent [10].…”
Section: Introductionmentioning
confidence: 99%